The Meaning of Denotation and Connotation in Lohidu Oral Literature in the Community in Tilamuta District, Boalemo Regency - Ishak Y. Majid; Asna Ntelu; Salam (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Lohidu is an oral literature in the form of pantun in the Gorontalo language that is usually sung in various places, such as in rice fields, at sea, in gardens, on lakes, or in certain traditional events. This study aims to describe the denotative and connotative meanings in the oral literature of lohidu in the community in Tilamuta District, Boalemo Regency. The method used in this study is a qualitative descriptive method. The research data are in the form of lines and stanzas of lohidu that contain denotative and connotative meanings. The data source is the community in Tilamuta District, Boalemo Regency. Data collection techniques are observation, recording, and note-taking techniques. Data analysis techniques are data transcription, data translation, identifying denotative and connotative meanings, presenting data, and concluding the research results. The results of the study indicate that the denotative meaning in Lohidu oral literature is found in words that refer directly to the literal and objective meaning of the word. The denotative meaning of Lohidu oral literature is found in the use of nouns, verbs, and adjectives to describe an event. For example, the word talohutu describes a person making something and the word ito’olo describes a number of people who are more than one. Meanwhile, the connotative meaning in Lohidu oral literature contains criticism of deviant behavior and life advice, such as religious negligence, arrogance, infidelity, and respect for parents.